Where the optimal balance is between public and private jobs: a qualitative study of graduates from university of Jaffna - Dilogini, S.; Thasika, Y. (University of Jaffna, 2024)
Throughout the qualitative study, researchers examined how graduates are demanding jobs to settle an optimal balance between public and private jobs. Findings are based on in-depth interviews with recently and earlier passed out graduates from University of Jaffna. In this study, researchers revealed how a job of graduates is finding an optimal balance, engaged in public and private jobs. Data were collected from 25 recently passed out and 25 earlier passed out graduates. First, researchers explored the situational and beneficial demands placed on those public and private jobs, along with the optimal balance that often results from those demands. Researchers then specified new model that reforms those job demands. To produce results, researchers developed a theoretical model of optimal balance between public and private jobs for graduates. Key findings of this study are the gaining of consciousness regarding to job selection underpinning stimuli and discover the balancing points between private and public jobs through inductive codes developed by researchers in this qualitative exploratory study.
Keywords: Demands; Graduates; Jobs; Optimal balance; Qualitative study